EFEKTIVITAS PENGGUNAAN MEDIA NUMBER FISH UNTUK MENGEMBANGKAN NUMERASI PADA ANAK USIA 3-4 TAHUN DI PAUD CAHAYA BUNDA PULAU BETUNG - Febriyanti; Trisnawati, Fitri Ayu; Harianja, Sri Indriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early childhood education plays an essential role in shaping children's character and cognitive abilities. Appropriate learning media, such as the Number Fish media, can enhance children's numerical skills in an enjoyable way. This study aims to describe the effectiveness of using Number Fish media in developing numeracy skills among children aged 3-4 years at PAUD Cahaya Bunda Pulau Betung. The research employs a qualitative approach with a descriptive method, collecting data through observation, interviews, and documentation. The results show that the Number Fish media is effective in improving children's understanding of numerical concepts through three stages of utilization: (1) Preparation Stage; (2) Implementation Stage; and (3) Evaluation/Reflection Stage. Children demonstrated significant cognitive development, including the ability to recognize numbers and understand their sequence. Additionally, this media supports the development of fine motor skills and children's social-emotional abilities. The teacher's role as a facilitator greatly influences the successful implementation of this media. Despite challenges such as differences in comprehension levels and limited resources, the use of Number Fish proves to be an effective solution for supporting early childhood education comprehensively.